Utilization of Floating Sludge (Oil and Fat) in The Meat Processing Industry as Raw Material for Catfish Pellets - Masteryna Maghfirahdina; Naniek Ratni J. A. R. (Yayasan Literasi Sains Indonesia, 2023)
One of the meat processing industries in Jombang Regency produces a significant amount of floating sludge waste (oil and fat) in its grease trap unit. If proper waste management is not carried out, environmental issues can arise. This article explores the potential use of floating sludge waste from meat processing industries as a raw material for catfish feed, with the aim of reducing waste, improving the economy, and reducing the production costs of catfish farming. Therefore, this research aims to analyze the best nutritional combination for catfish feed made from waste from the meat processing industry, tofu dregs, organic vegetables, and discarded eggs. The method used is fermentation with EM4 and sugarcane molasses, along with the addition of other waste materials to enhance the nutritional quality of the feed produced. There are five variations of feed compositions analyzed using proximate analysis and compared with SNI 01-4087-2006 concerning Quality Requirements for Dumbo Catfish Feed. The results show that several combinations of ingredients can meet most of the catfish feed quality standards, with the best option is K3 feed that made from floating sludge and discarded egg waste. Although, protein content is still below the standard, this combination has the potential to reduce the cost of catfish farming. This article encourages the development of sustainable, environmentally friendly alternative feeds and the potential reduction of industrial waste.